2021
DOI: 10.3389/fnut.2020.612115
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Diet and the Epigenome in the Pathogenesis of Type-1 Diabetes

Abstract: The autoimmune disease, Type 1 Diabetes Mellitus (T1DM), results in the destruction of pancreatic β-cells, and the International Diabetes Federation reports that its incidence is increasing worldwide. T1DM is a complex disease due to the interaction between genetic and environmental factors. Certain dietary patterns and nutrients are known to cause epigenetic modifications in physiological conditions and diseases. However, the interplay between diet and epigenetics is not yet well-understood in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 118 publications
1
14
0
Order By: Relevance
“…This was in accordance to the observation of Kalra and Dhingra ( 15 ), who reported the hypothesis that exposure to A1/A1 β-CN milk of exotic breeds, such as those from India, might be linked with the rising incidence of type 1 diabetes. On the same topic, Kohil et al ( 25 ) concluded that specific dietary patterns can exert a direct impact on pathogenesis of type 1 diabetes through epigenetic modifications and that BCM-7 could act as an epigenetic modulator, differentially methylating genes involved in type 1 diabetes development. However, more recently, both Aslam et al ( 17 ) and Hegde ( 18 ) concluded that there was no clear evidence linking BCM-7 intake with type 1 diabetes, cardiovascular disease and neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
“…This was in accordance to the observation of Kalra and Dhingra ( 15 ), who reported the hypothesis that exposure to A1/A1 β-CN milk of exotic breeds, such as those from India, might be linked with the rising incidence of type 1 diabetes. On the same topic, Kohil et al ( 25 ) concluded that specific dietary patterns can exert a direct impact on pathogenesis of type 1 diabetes through epigenetic modifications and that BCM-7 could act as an epigenetic modulator, differentially methylating genes involved in type 1 diabetes development. However, more recently, both Aslam et al ( 17 ) and Hegde ( 18 ) concluded that there was no clear evidence linking BCM-7 intake with type 1 diabetes, cardiovascular disease and neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis behind the controversy is that A1 betacasein may increase the risk of DM-1 in genetically susceptible children with the release of opioid peptide, BCM-7, which affects the immune system and produces autoantibodies against β-cells of the pancreas. Also, BCM-7 through epigenetic modulation found to be differentially methylated genes that predispose DM-1 [17]. In a case-control study in Finland, the early introduction of bovine milk resulted in an increased risk of DM-1 by 2 times [37].…”
Section: Type 1 Diabetes (Dm-1)mentioning
confidence: 99%
“…The protein tyrosine phosphatase non-receptor type 22 (PTPN22) gene on chromosome 1p13 exhibits polymorphisms and encodes lymphoid specific phosphatase (LYP) [ 93 ]. LYP suppresses activation of T cells and is linked with T1D [ 68 ]. On the other hand, the interferon induced helicase 1 (IFIH1), interleukin-2 receptor subunit alpha (IL2RA), ubiquitin associated SH3 domain containing protein A (UBASH3A) and basic leucine zipper transcription factor 2 (BACH2) are important genetic loci associated with T1D [ 23 , 24 , 114 , 121 ].…”
Section: Genetic Regulations Of Diabetesmentioning
confidence: 99%
“…Environmental factors control the activation or inhibition of a particular gene expression by regulating transcription factor accessibility to DNA. Among epigenetic modifications, DNA methylation, histone modifications and altered microRNA mediated genetic expression trigger the onset of several autoimmune disorders including T1D [ 68 ]. The main environmental factors responsible for onset of T2D are intra-utero environments, advancement of age, low birth weight, obesity of mother that ultimately cause intrauterine growth retardation (IUGR) of child [ 63 ].…”
Section: Epigenetic Influence In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation